Dennis Brown : Remember me always (United Kingdom : Keeling Reggae)
Dennis Brown, who is Dennis Brown? A legend, an icon, crowned Prince of Reggae never since Bob Marley there is reggae artiste that is so conscious, singing hits like Silhouettes, Promise land, Wild fire and many more.
Keywords: Reggae; Dennis Brown, 1945-1999.